2022
DOI: 10.1097/ajp.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transition to Virtual Assessment and Treatment in an Interdisciplinary Randomized Clinical Trial for Youth With Chronic Pain

Abstract: Objectives: COVID-19 abruptly halted in-person clinical care and research requiring a shift to virtual assessment and treatment. This unexpected transition of a 2-arm randomized controlled trial (RCT) examining interdisciplinary graded exposure treatment (GET Living) compared with multidisciplinary pain management for youth with chronic pain provided an opportunity to implement the first remotely delivered exposure treatment and remotely delivered biomechanical assessment for pediatric chronic pain. Here we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…With the onset of the COVID-19 pandemic, this trial swiftly transitioned to video delivered care 50 with the field broadly encouraging this approach to ensure continued support and treatment of vulnerable youth living with chronic pain and their families. 3,11,47 Before the pandemic, remotely delivered pain treatment centered on digital tools 13 with essentially no evidence for video delivery of multidisciplinary pain treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the onset of the COVID-19 pandemic, this trial swiftly transitioned to video delivered care 50 with the field broadly encouraging this approach to ensure continued support and treatment of vulnerable youth living with chronic pain and their families. 3,11,47 Before the pandemic, remotely delivered pain treatment centered on digital tools 13 with essentially no evidence for video delivery of multidisciplinary pain treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding this transition are previously published. 50 In March 2021, in person treatment resumed. Owing to interest from families for a video option and enhanced access for families in distant and underresourced areas, patients could choose to enroll in video or in person treatment after that date.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, 89.9% of the participants in the 2020 US Pain Foundation survey indicated that increased access to telehealth following the COVID-19 outbreak improved their ability to obtain services and expressed a desire for telehealth to remain a treatment modality beyond the pandemic. Further, it is well documented that telehealth and in-person multidisciplinary pediatric pain care may have equivalent and comparable efficacy with regard to outcomes and treatment engagement 13–15 …”
mentioning
confidence: 99%
“…Further, it is well documented that telehealth and in-person multidisciplinary pediatric pain care may have equivalent and comparable efficacy with regard to outcomes and treatment engagement. [13][14][15] Before the rapid shift to primarily telehealth services in 2020, individuals wanting pain management services at a multidisciplinary clinic often needed to live locally or have the resources to commute to their nearest clinic. Youth with chronic pain endure high symptom burden while awaiting multidisciplinary evaluation 16 and have improved painrelated outcomes following evaluation, 17 which often leads to multidisciplinary treatment.…”
mentioning
confidence: 99%